Masculinity in Stephen Graham & Jack Thorne’s Film Adolescence - Yosi Evelyn Tondang; Nabila Shaini Putri; Annisa Ananda; Syamsul Bahri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
From past to present, masculinity has continuously shaped how men are expected to behave in society, especially in adolescence. The television series Adolescence highlights these expectations by portraying different male characters in their daily interactions, reflecting how masculinity operates in real life. This study aims to explore the types of masculinity displayed in the series based on R.W. Connell’s theory (2005), which classifies masculinity into hegemonic, complicit, subordinate, and marginalized types. The research applies a qualitative descriptive method to examine social realities through selected dialogues and scenes. The findings reveal that hegemonic masculinity (64%) is the most frequently represented form, where dominance, toughness, and emotional restraint are highlighted as masculine ideals. Subordinate masculinity (27%) follows, showing that expressions such as emotional openness or queerness are still viewed as less masculine. Marginalized masculinity (9%) appears in contexts involving race and class, while complicit masculinity (5%) is rarely shown, suggesting that most characters either fully embody or struggle against dominant norms. The data shows how the media continues to uphold hegemonic masculinity while only subtly acknowledging its alternatives, offering insight into the gender dynamics experienced by teenage boys today.